Test for Formalin Content in Consumed Fish at Several Traditional Markets in Surakarta Using Natural Extract of Dragon Fruit Peel - Avivi Khoirunnida; Tri Wiharti; Ratna Dewi Eskundari (Jurnal Biologi Tropis, 2023)
Food has an expiration date. To make food have a longer shelf life, food manufacturers use preservatives as a solution. There are preservatives that are safe to use and prohibited from being used. One of the chemical preservatives prohibited from being used in food is formalin. Formalin is usually added to processed meat and fish foods. The purpose of this study was to detect the presence of formaldehyde as a preservative in consumption fish sold in several markets in Surakarta. The method used in this study is experimental. As an indicator in this study, natural ingredients were used, namely dragon fruit peel extract. This research is expected to be a solution and an alternative in detecting formaldehyde content and an effort to choose healthy consumption fish without containing harmful chemicals. The results of this study found fish containing formaldehyde, namely shark, salmon, tilapia, mackerel, and flying fish. If consumed in the long term, formalin can cause damage to kidney function, liver and cause cancer.